2011
DOI: 10.1039/c0cp02401e
|View full text |Cite
|
Sign up to set email alerts
|

Study of host–guest interactions in benzodiazacoronands by means of solid state NMR spectroscopy, X-ray diffraction and quantum mechanical computations

Abstract: In this work we present solid state data for five host-guest complexes formed by N-(4,19-dioxo-2,8,15,21-tetraoxa-5,18-diazatricyclohexacosa-1(25),9(14),10,12,22(26),23-hexaen-26-yl)-benzamide (1) belonging to the group of benzodiazacoronands, achiral compounds for which chiral crystals were found (J. Kalisiak and J. Jurczak, Cryst. Growth Des., 2006, 6, 20). The X-ray structure was resolved for four of them. It was found that 1 crystallizes in P2(1)/c, P1 and P2(1)/n achiral space groups. Differentiation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…1). The crystal structure shows "host-guest" interactions in which the HHSB molecule is a host [31].…”
Section: The Solid State Structure Of Hhsbmentioning
confidence: 98%
“…1). The crystal structure shows "host-guest" interactions in which the HHSB molecule is a host [31].…”
Section: The Solid State Structure Of Hhsbmentioning
confidence: 98%
“…Recently, our interest has been focused on the preparation of chiral macrocyclic compounds, which are stable in solution and solid state. As we revealed, the benzodiazacoronads, which belong to the class of compounds with planar chirality, are promising candidates for such a project. In the course of our studies, we have found that atropoisomers of benzodiazacoronands can exist in solution if two independent, indispensable requirements are met: first, the presence of a large intra-annular group that cannot pass through the macroring plane and thus defines its top and bottom side; second, the presence of a group that differentiates between the left and right side of the macrocycle (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…However, to date only a few neutral, efficient receptors for the above-mentioned anions operating in demanding solvents, suitable for practical application, have been identified . One successful strategy for developing such receptors is to use the chemistry of cryptands, as has recently been shown by Bowman-James et al In our laboratory we obtained compounds, structurally related to cryptands, that are in principle macrocycles with a flexible substituent–lariat arm . In the study reported here, we designed, obtained, and studied the properties of this new class of putative anion receptors 1 – 4 (Figure ), which we have called “unclosed cryptands”.…”
mentioning
confidence: 96%